(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The aim was to develop a new improved Sorbent system (S-S) from organic sorbent material, nutrients, biosurfactant and microbial cell producing it for bioremediation of heavy oil hydrocarbons in various soil types. New sorbent material (S-M) was developed from paper mill short waste fibers because it requires very low energy to manufacture and the production costs of this S-M is extremely low compared to similar products in the market. S-M has good sorption characteristics for various oil products, is fully biodegradable, can be applied at sensitive environmental areas. S-M can be combined with microorganisms producing biosurfactant. The goal of investigations was to optimize S-S composition to minimize the leakage of heavy hydrocarbons to deeper soil layers or ground water. The optimal composition of S-S for all types of soil was determined: S-M 86.3-89.3%, microorganisms producing biosurfactant ≥ 107 CFU/g, biosurfactant solution – 3%, nutrients (nitrogen and phosphorous) 0.5 and 0.2%. Recommended optimal S-S moisture is 7%.